Clontuskert Augustinian Priory, interior, east window, jamb - O'Donovan, Danielle (My University, 2009)
Jamb shaft running along reveal of east window. Moulding comprises, from angle: corner triple filleted roll flanked at either side by hollows and chamfers. This moulding looks Early English but is most likely fifteenth century, it looks similar to the work at Roscommon Dominican Friary, both in the jambs and in the tracery (both broken but reconstructions exist at site and on paper).
East window
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Augustinian; Tracery (Architecture); roll-and-fillet moldings; moldings, hollow; fillets (moldings); bar tracery